EXAMINING OF E-MARKETING, INFORMATION SYSTEM AND UNIVERSITY BRAND IMAGE ON STUDENT DECISION - Rizan Machmud; David P.E. Saerang; Agus Supandi; Rudy S Wenas (AIBPM Publisher, 2018)
The large number of higher education in Indonesia, forced higher education especially universty to improve its competitiveness to maintain its students as consumers. One of the history of education in Indonesia is the issuance of Presidential Decree of the Republic of Indonesia Number 93 year 1999 which